English Pre-Service Teachers’ Perception on PLP Program in 2020 - Mirna Wati; Dewi Nopita; Muhammad Candra (Juliet, 2022)
This study aimed to find out English pre-service teachers’ perception on PLP program in 2020. Descriptive qualitative is a research design for this research. An object of this research is the PLP program implemented by Universitas Maritim Raja Ali Haji in 2020. The data was taken from the ninth semester consisting 37 students by using purposive sampling. The instrument for collecting data are open-ended and close-ended questionnaires. The result of the study showed that the participants are following all of the PLP program’s requirements. However, there are certain program demands that are not met in a pandemic situation in accordance with the program’s objective.